Bio-briquettes Derived from Rice Husks and Mushroom Cultivation Materials - Ika Nawang Puspitawati; Sani; Suprihatin; Mutasim Billah; Caecillia P udjiastuti; AR Yelvia (Nusantara Science and Technology Proceedings, 2023)
The bio briquette is a type of briquette that is derived from agricultural waste since it is intentionally produced using biomass charcoal. The processing of agricultural waste, such as mushroom planting material, into bio briquettes is characterized by its low cost. When bio briquettes undergo appropriate and accurate processing, they can yield briquettes of superior quality. The primary objective of this research endeavor was to generate a biobriquette using an agricultural byproduct derived from mushroom farming, while concurrently assessing the distinct attributes and properties of said biobriquette. The research utilized a total of 400 grams of waste from mushroom culture materials, together with an adhesive composed of 40 grams of starch. The briquette dough is subsequently extruded in a cylindrical shape. Subsequently, the mold briquettes are subjected to a heating process at a temperature of 80°C for 5 hours, to decrease the moisture content. The outcome of the smoke test indicates that the emission of smoke will cease after 75 seconds. In the conducted Combustion of Speed Test, the obtained findings indicate a combustion rate of 0.425 grams per minute, using an initial sample weight of 5.8 grams. The ash content yielded a reading of 10.6%.